A review on the bioenergetics of anaerobic microbial metabolism close to the thermodynamic limits and its implications for digestion applications. (January 2018) - Leng, Ling; Yang, Peixian; Singh, Shubham; Zhuang, Huichuan; Xu, Linji; Chen, Wen-Hsing; Dolfing, Jan; Li, Dong; Zhang, Yan; Zeng, Huiping; Chu, Wei; Lee, Po-Heng
Highlights: Functional microorganisms and syntroph partners in anaerobic digestion. Kinetic parameters of propionate degradation to methane and microbial growth. Thermodynamics of propionate degradation and the reversibility of acetate oxidation. Metabolic pathways and energy conservation of syntrophs in anaerobic digestion. Pathways of mediated and direct interspecies electron transfer. Abstract: The exploration of the energetics of anaerobic digestion systems can reveal how microorganisms cooperate efficiently for cell growth and methane production, especially under low-substrate conditions. The establishment of a thermodynamically interdependent partnership, called anaerobic syntrophy, allows unfavorable reactions to proceed. Interspecies electron transfer and the concentrations of electron carriers are crucial for maintaining this mutualistic activity. This critical review summarizes the functional microorganisms and syntroph partners, particularly in the metabolic pathways and energy conservation of syntrophs. The kinetics and thermodynamics of propionate degradation to methane, reversibility of the acetate oxidation process, and estimation of microbial growth are summarized. The various routes of interspecies electron transfer, reverse electron transfer, and Poly-β-hydroxyalkanoate formation in the syntrophic community are also reviewed. Finally, promising and critical directions of future research are proposed. Fundamental insight in the activities and interactions involved in AD systems could serve as a guidance for engineered systems optimization and upgrade.